The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11011-021-00790-9
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary and non-hereditary etiologies associated with extensive brain calcification: case series

Abstract: Cerebral calcification may be caused by several potentially treatable conditions, however, in most cases it does not receive special attention in clinical practice. From the point of view of etiology, the diseases associated with cerebral calcification can be divided into two main groups: idiopathic (mostly incurable) and secondary (potentially treatable). The first group includes mainly the hereditary diseases identified before 2021 (primary familial brain calcification subtypes, previously known as Fahr's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…During the last two decades, studies have reported associations between BGC and CMV, chronic active EBV, HIV, Mycobacterium tuberculosis, rubella virus, and Zika virus . Narrative reviews and textbooks have reported associations between BGC and Brucella sp., HSV, mumps virus, Neisseria meningitidis, Taenia solium, Toxoplasma gondii, and Treponema pallidum [2][3][4]6,7,17,38,41,[43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Most original studies reported about congenital or perinatally acquired infectious diseases (CMV, HIV, rubella virus, Zika virus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, studies have reported associations between BGC and CMV, chronic active EBV, HIV, Mycobacterium tuberculosis, rubella virus, and Zika virus . Narrative reviews and textbooks have reported associations between BGC and Brucella sp., HSV, mumps virus, Neisseria meningitidis, Taenia solium, Toxoplasma gondii, and Treponema pallidum [2][3][4]6,7,17,38,41,[43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Most original studies reported about congenital or perinatally acquired infectious diseases (CMV, HIV, rubella virus, Zika virus).…”
Section: Discussionmentioning
confidence: 99%
“…Narrative reviews and textbooks reported an additional seven pathogens, which included Brucella sp., HSV, mumps virus, Neisseria meningitidis, Taenia solium (a tapeworm causing cysticercosis), Toxoplasma gondii, and Treponema pallidum [2][3][4]6,7,17,38,41,[43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. The original articles, which were cited by the narrative reviews and textbooks, were published before 2002 and were therefore not retrieved.…”
Section: Other Infectionsmentioning
confidence: 99%